PhET interactive simulation approach in teaching electricity and magnetism among science teacher education students - Marshall James P. Dantic; Alyssa Fluraon (Journal of Science and Education)
By boosting students' thinking and understanding of hard ideas, innovative teaching pedagogies help them better comprehend difficult subjects in Physics. This study aimed to assess the students’ conceptual knowledge in electricity and magnetism and their perspectives on the effects of the Phet Simulation Approach in teaching the said concepts. It utilized educational action research design with assessment-tests and a structured-interview guide as the main instruments in gathering the required data. There are 14 science teacher education students whose taking electricity and magnetism as their major subject served as participants. The assessment-test is composed of the traditional assessment test or multiple-choice test composed of 60 questions. The structured-interview guide contains one question, "What are the effects of Phet Simulation Approach in learning Electricity and Magnetism?” The results have revealed that the conceptual knowledge in Electricity and Magnetism improved to very satisfactory after the application of intervention. There is a significant difference in the assessment scores between pre-test and posttest. Six themes emerged from the students' perspectives on the effects of the intervention, including (a) better understanding; (b) learning through visualization; (c) learning became fun; (d) promotes self-facilitation of learning; (e) provides a broader range of options; and (f) grasping the micro-scale concepts. The study concludes that PhET Simulation Approach is an effective teaching strategy in electricity and magnetism. Further, the strategy is positively accepted by the students based on the qualitative data.